Tissue Culture Applications of Artemisia annua L. Callus for Indirect Organogenesis and Production Phytochemical (Plant Tissue Culture and Biotechnology, 2020)
Artemisia annua L. axenic plants were used to induce callogeneisis for production of phenolics and plant regeneration. Up to 95% callogenesis from leaf and stem explants on MS supplemented with 2.0 mg/l NAA or 2,4-D + 0.2 mg/l BAP (MSC1 and MSC2) was observed. Lower callus frequency but with improved embryogenic potential was observed upon subculture on medium with reduced auxin and increased BAP concentration (0.5 mg/l NAA or 2,4-D + 0.5 mg/l BAP) (MSC3 and MSC4). The leafinduced callus on NAA/BAP (MSC3) showed best antioxidant potential. Induced shoot regeneration occurred upon high concentration BAP combined with NAA rather than with 2,4-D (0.25 mg/l NAA or 2,4-D + 1.0 mg/l BAP, MSR 1 and MSR2, respectively). Optimal shoot multiplication and rooting were obtained on 1.0 mg/l BAP and 0.1 mg/l IBA, respectively, followed by acclimatization of regenerants to greenhouse conditions. This work aims at establishing protocol for A. annua preservation and biosynthesis of natural products.Plant Tissue Cult. & Biotech. 30(1): 97-106, 2020 (June)